University Sports Association as the way to sport activity development among Silesian students - Anna Mędrak; Michał Rżany; Barbara Otremba; Elwira Brodowska; Magdalena Szynal; Magdalena Alcer; Anna Górecka; Tomasz Stefaniak; Krzysztof Suszyński; Dariusz Górka (Nicolaus Copernicus University in Toruń, 2015)
Introduction. There are two fundaments of healthy lifestyle philosophy: regular physical activity and proper diet. The development of physical activity among students is determined by many complex factors. We can distinguish certain aspects such as university profile, access to the sport facilities and the opportunity to participate in sport activities which are organized by sport clubs or University Sports Association. The aim of the study. The aim of the study was to analyze the factors that affect self-assessment of students physical activity. The following questions have been asked: 1.Is the choice of the university related to the access to sport activities which are organized by University Sport Association? 2.Does the participating in activities, which are organized by University Sport Association, help in physical development? 3.Is there any relation between the location, time, type, the way of sport activities which are offered by University Sport Association and participating in them? Material and methods. 395 students took part in research: 257 women (18-27 years old) (x=20,7 ; SD=1,4) and 108 men (18-26 years old) (x=21; SD=1,45). All the students are from five Silesian universities. Method used for the research was the anonymous questionnaire consisting of 37 questions which concerned: the way of the physical activity taken by students, the issue of University Sport Association and the influence of the university profile on physical activity development. The Likert scale was used in 21 questions. Statistical description included descriptive statistics. Degree of difference was defined by ANOVA analysis. Results. Descriptive analysis showed significant dependence between the type of the university and the location of sport facilities (p=0,04). The type of the university has no influence on the factors like: time (p=0,07) and type of sport activities offered by University Sport Association (p=0,39). There is also an important connection between the type of the university and resignation from doing sport (p=0,0002). Mostly - Medical University of Silesia students, least frequently - University of Silesia students. There is dependence between approach to doing sport among students and the type of university (p=0,01). The university which helps the most in sport career is University of Economics in Katowice. Conclusions: 1.Taking the physical activity by student depends on location of the university and sport facilities. 2.The factors such as time and type of sport activities are not related to the type of the university. 3.The type of the university influence the resignation from doing sport by students.